Posisi Strategis Pendidikan Tinggi Dalam Pembangunan Ekonomi - Agustuti Handayani (PUBLICA, 2012)
Theory development in the past embraces the principle that poverty occurs because of a lack of ability to save and build physical capital. However, the theory was later corrected by another theory which states that "quality" as the ability of resident physical and psychological-intellectual, is more important than physical capital in the development process. The theory asserts that human resources (HR) is the most decisive factor of the character and pace of social and economic development of a nation Thus, an increase in resident enrollment to pursue higher education should be a strategic agenda for a nation to rise up to pursue economic progress.